Jovens em Cuiabá : identidade e subjetividade através do consumo do Streaming - Oliveira, Hanna Thryccia de Almeida (2022)
Generation Z grew up in the technological environment, always connected to the flow of information on social networks and artistic products linked through Streaming. Most young people are unaware of a world without technology, and a life without the internet for many seems surreal. The immediatist culture is related to contemporaneity, fostered by the infinite information and by the connectivity in networks among society, and this culture influences the way in which the structure of the past, present and future is seen by the world. Immediacy also changes social relations, the economy, politics and ecology, as more and more decisions are made without evaluating the long-term consequences, only thinking about the now, in the moment. The aim of this research is to understand (post) modern subjectivity and the identity issue of young people through consumption habits derived from Streaming in Cuiabá, through a specific delimitation within Generation Z. The general objective of this research is to identify how the habits of consumption of artistic products and derivatives converge to the identity issue of young people aged 20 to 24 in Cuiabá. It should be noted that the artistic products in question are the two TV series chosen, and the specific objectives of this research are: to trace the Streaming consumer profile of young people from Cuiaba; to know the artistic products (TV series) and derived products that are consumed; and point out social and cultural aspects that affect consumption, and that are possibly affected by consumption. The methodology consisted of bibliographic research and field research through electronic surveys. Both series come from streaming services: Netflix's Stranger Things and Disney Plus' The Mandalorian. It is intended through this research to map the consumption of these series and their derivatives, and how these products shape (even if subjectively) the personality of young people and teenagers, revealing meanings based on these cultural attributes. Evidence was found that the consumption of these products influences the image and personal identity of young people, and the methodology and questionnaire applied in this research can be applied to other social groups.